Prevalence of Plasmodium spp. in malaria asymptomatic African migrants assessed by nucleic acid sequence based amplification - Marangi, Marianna; Di Tullio, Rocco; Mens, Pètra F; Martinelli, Domenico; Fazio, Vincenzina; Angarano, Gioacchino; Schallig, Henk DFH; Giangaspero, Annunziata; Scotto, Gaetano (Malaria journal, 2009)
Background Malaria is one of the most important infectious diseases in the world. Although most cases are found distributed in the tropical regions of Africa, Asia, Central and South Americas, there is in Europe a significant increase in the number of imported cases in non-endemic countries, in particular due to the higher mobility in today's society. Methods The prevalence of a possible asymptomatic infection with Plasmodium species was assessed using Nucleic Acid Sequence Based Amplification (NASBA) assays on clinical samples collected from 195 study cases with no clinical signs related to malaria and coming from sub-Saharan African regions to Southern Italy. In addition, base-line demographic, clinical and socio-economic information was collected from study participants who also underwent a full clinical examination. Results Sixty-two study subjects (31.8%) were found positive for Plasmodium using a pan Plasmodium specific NASBA which can detect all four Plasmodium species causing human disease, based on the small subunit 18S rRNA gene (18S NASBA). Twenty-four samples (38%) of the 62 18S NASBA positive study cases were found positive with a Pfs25 mRNA NASBA, which is specific for the detection of gametocytes of Plasmodium falciparum . A statistically significant association was observed between 18S NASBA positivity and splenomegaly, hepatomegaly and leukopaenia and country of origin. Conclusion This study showed that a substantial proportion of people originating from malaria endemic countries harbor malaria parasites in their blood. If transmission conditions are available, they could potentially be a reservoir. Thefore, health authorities should pay special attention to the health of this potential risk group and aim to improve their health conditions.